Decadal Trends in Polycyclic Aromatic Hydrocarbon (PAH) Contamination Assessed by 1-Hydroxypyrene in Fish Bile Fluid in the Netherlands: Declining in Marine Waters but Still a Concern in Estuaries - Vethaak, A. Dick; Baggelaar, Paul K.; van Lieverloo, J. Hein M.; Ariese, Freek (Frontiers in Marine Science, 2016)
Long-term monitoring data on the concentrations of biliary 1-hydroxypyrene (1-OHPyr) in flatfish, as a biomarker for polycyclic aromatic hydrocarbon (PAH) exposure, were analysed and evaluated to elucidate spatial differences and temporal trends in marine and estuarine PAH contamination in the Netherlands. Dab (Limanda limanda) and flounder (Platichthys flesus) with partly overlapping distributions were used as target species. In total 1831 bile samples were analysed individually: 417 dab in 1998-2005 and 1438 flounder in 1996-2012. The sampling procedure for flatfish and the PAH metabolites determination by means of high performance liquid chromatography (HPLC) with fluorescence (FL) detection were based on international guidelines. Measuring the absorbance at 380 nm was tested to correct for possible differences in feeding status, but this turned out not to be a suitable parameter for the standardisation of PAH metabolite concentrations. Both fish species showed statistically significant differences in biliary 1-OHPyr concentrations between various locations. The highest level of PAH contamination was found in flounder from the estuarine Western Scheldt, which might be partly due to local dredging activities. Dab from the central North Sea (Dogger Bank) showed the lowest level of PAH contamination. Analysis of all the data indicated mainly downward trends in PAH contamination, most clearly pronounced in the Dutch Wadden Sea. PAH exposure levels in the Dutch coastal waters including the Eastern Scheldt and the Wadden Sea, and also at the offshore North Sea monitoring sites represent levels of response that are not indicative of significant harm. In contrast, PAH contamination in the more industrialised Dutch estuaries (Western Scheldt and Ems Dollard) is still a cause for concern. Future monitoring should register the total bile volume, the sex of the fish and the method of fishing to improve the interpretation of the data. In addition, the biliary absorbance at 380 nm should be registered as it may help the interpretation of outliers in the data.